Environmental Destruction As A Weapon of War: A Human Rights and Humanitarian Law Perspective - Baskoro, Aji (Alauddin Law Development Journal (ALDEV), 2025)
Environmental destruction as a war tactic poses significant challenges under international law. This study explores the intersection of International Humanitarian Law (IHL) and International Human Rights Law (IHRL) in addressing war-induced ecological harm, emphasizing “environcide” as a human rights violation. Using a normative juridical method, this research examines legal frameworks, including the ENMOD Convention, Geneva Conventions, and Rome Statute, alongside case studies from Vietnam, Ukraine-Russia, and Gaza. Employing a statute approach and Critical Legal Studies (CLS) analysis, the study reveals structural inequalities and power dynamics that hinder legal enforcement. It also identifies opportunities to strengthen accountability, recognize environcide, and promote participatory legal reforms. Aligning IHL and IHRL through these mechanisms can enhance environmental protection during and after conflict, ensuring a more just and sustainable approach to war’s ecological consequences.